Rhetorical stages and linguistic mechanisms in forestry research reports - Renu Joseph (2017)
Research articles constitute a key genre because of their central role in the communication of new knowledge in all academic disciplines. Researchers are often evaluated on the basis of their publications in peer-reviewed journals, and their professional advancement depends on their ability to conform to the rhetorical requirements and language conventions set by journals. However, novice researchers and second language learners of English often lack the writing skills necessary to meet the editorial standards of top-tier international journals. It is therefore necessary to examine the works of expert writers to identify the rhetorical stages and language mechanisms used by them so that we can create a framework that novice writers can follow. Although numerous studies have used genre analysis to study research articles in various disciplines, no study to date has analysed research articles in Forestry. This study aims to identify the schematic structures and linguistic mechanisms employed in Forestry research reports in order to create a pedagogically applicable model. A genre-based analysis based on Swales’ (1990, 2004) move-step analysis framework was used to study 60 empirical research reports in Forestry following the Introduction-Methods-Results-Discussion structure. The researcher also interviewed eight specialist informants in the field of Forestry to seek additional information which could not be obtained via textual analysis. The analysis indicates that the generic structure of Forestry research reports incorporate a total of 20 rhetorical moves and 41 steps. Although the Introduction section reflects Swales’ (2004) CARS model at the move-level, differences are evident at the step level. The obligatory and quasi-obligatory moves in the Methods section include those describing research sites, sampling procedures, data collection procedures and data analysis procedures. The analysis of the Results section reveals a three-move structure in which authors set a stage for their results before presenting findings and comments on their findings. About paving the way for results, only the description of data analysis procedures constitutes a principal step, while the only comments that are relevant in the Results section include (1) the explanations for findings and (ii) the evaluation of the study which emphasises limitations and advantages. The Discussion section focuses on establishing links between new and existing knowledge by comparing current findings with the findings of past research. It also focuses on furthering disciplinary knowledge through recommendations for practical applications and directions for future research. This study has identified the salient and recurring linguistic mechanisms in every step and discussed them with related examples. Inter-disciplinary differences and similarities have also been revealed via comparisons between the generic structure of Forestry research reports and those reported by previous researchers for other disciplines. This study shows that varying degrees of emphasis is required for different rhetorical steps while English language instructors design teaching materials aimed at guiding learners in writing Forestry research reports.